Hydrothermal synthesis and tunable luminescence of CaSiO3:RE3+(RE3+ = Eu3+, Sm3+, Tb3+, Dy3+) nanocrystals. (May 2015) - Fu, Linlin; Yang, Xingxing; Fu, Zuoling; Wu, Zhijian; Jeong, Jung Hyun
Graphical abstract: Highlights: Near-spherical CaSiO3 nanocrystals were synthesized via a hydrothermal method. The effect of calcination temperature on crystalline phase formation was discussed. Optical properties of trivalent ions doped CaSiO3 nanocrystals were investigated. Tunable luminescence of CaSiO3 :Tb 3+, Eu 3+ can be achieved by a simple method. Abstract: CaSiO3 :RE 3+ (RE 3+  = Eu 3+, Sm 3+, Tb 3+, Dy 3+ ) nanocrystals were prepared by facile hydrothermal method with further calcinations. The crystal structure and the effects of annealing temperature on phase transition have been characterized by X-ray diffraction (XRD). The photoluminescence (PL) and PL excitation (PLE) spectra were used to characterize the optical properties of all samples. The effect of Eu 3+ and Sm 3+ doping concentrations on the luminescent intensity were also investigated in details, respectively. Moreover, the luminescence colors of the Tb 3+ and Eu 3+ co-doped CaSiO3 samples can be tuned by simply adjusting the relative doping concentrations of the rare earth ions under a single wavelength excitation, which might find potential applications in the fields of light display systems and optoelectronic devices.